Applying the Analog Configurability Test Approach in a Wireless Sensor Network Application - Agustín Laprovitta; Gabriela Peretti; Eduardo Romero (Journal of Electrical and Computer Engineering)
This work addresses the application of the analog configurability test (ACT) approach for an embedded analog configurable circuit (EACC), composed of operational amplifiers and interconnection resources that are embedded in the MSP430xG461x microcontrollers family. This test strategy is particularly useful for in-field application requiring reliability, safe operation, or fault tolerance characteristics. Our test proposal consists of programming a reduced set of available configurations for the EACC and testing its functionality by measuring only a few key parameters. The processor executes an embedded test routine that sequentially programs selected configurations, sets the test stimulus, acquires data from the internal ADC, and performs required calculations. The test approach is experimentally evaluated using an embedded system-based real application board. Our experimental results show very good repeatability, with very low errors. These results show that the ACT proposed here is useful for testing the functionality of the circuit under test in a real application context by using a simple strategy at a very low cost.